2009
DOI: 10.1021/la9028047
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Colloids Synthesized with Nanofluidic Technology

Abstract: Limitations in the methods employed to generate micrometric colloidal droplets hinder the emergence of key applications in the fields of material science and drug delivery. Through the use of dedicated nanofluidic devices and by taking advantage of an original physical effect called capillary focusing, we could circumvent some of these limitations. The nanofluidic (i.e., submicrometric) devices introduced herein are made of soft materials, and their fabrication relies upon rapid technologies. The objects that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
120
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 36 publications
(32 reference statements)
4
120
0
Order By: Relevance
“…This breakup mechanism also explains the droplet formation at a step change in the microchannel depth, known as step emulsification (24)(25)(26)(27). As in those cases of a sudden step, the size of the drop that is formed decreases linearly with the channel height, which allows micrometer-scale droplets to be reached by using equivalently thin channels (24,26).…”
Section: Physical Mechanism For Droplet Breakupmentioning
confidence: 95%
See 1 more Smart Citation
“…This breakup mechanism also explains the droplet formation at a step change in the microchannel depth, known as step emulsification (24)(25)(26)(27). As in those cases of a sudden step, the size of the drop that is formed decreases linearly with the channel height, which allows micrometer-scale droplets to be reached by using equivalently thin channels (24,26).…”
Section: Physical Mechanism For Droplet Breakupmentioning
confidence: 95%
“…As in those cases of a sudden step, the size of the drop that is formed decreases linearly with the channel height, which allows micrometer-scale droplets to be reached by using equivalently thin channels (24,26). In contrast, however, the value of the slope here provides an additional control parameter to tune the drop size.…”
Section: Physical Mechanism For Droplet Breakupmentioning
confidence: 99%
“…It is the elaborate chip design that allowed researchers not only to miniaturize microchannel emulsification reactors and prepare narrowly monodisperse spherical beads but also to achieve unprecedented control over structure and shape of particles. This unique capability of control resulted in the realization of perfectly controlled multiple emulsions [136][137][138][139][140][141][142][143][144][145], Janus particles [146][147][148][149][150][151][152][153][154][155][156], regular nonspherical shapes [157][158][159][160][161][162][163][164][165][166] and even gas bubbles [167][168][169][170][171], almost all of which were impossible to achieve before.…”
Section: Microfluidics: the Ultimate Controlmentioning
confidence: 99%
“…Smaller monodisperse droplets can be produced at a nano-microchannel interface where the dispersed phase is forced through the nanochannel and when it reaches the microchannel, it destabilizes due to capillary instability and breaks up into monodisperse droplets 191,192 . It was shown that the droplet size scales linearly with the height of the nanochannel 191,193 and it was also shown that it is feasible to produce monodisperse droplets with sizes down to 400 nm 194 . The production rates for a single nano-microchannel interface were shown to be limited to approximately 10 3 droplets per second 193 .…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the droplet size scales linearly with the height of the nanochannel 191,193 and it was also shown that it is feasible to produce monodisperse droplets with sizes down to 400 nm 194 . The production rates for a single nano-microchannel interface were shown to be limited to approximately 10 3 droplets per second 193 .…”
Section: Introductionmentioning
confidence: 99%